Chapter Incomplete parenthesis An overview - Kluck, Marlies (De Gruyter, 2014)
While customarily considered 'peripheral' linguistic phenomena, both parenthesis and ellipsis raise interesting and far-reaching theoretical questions. It is worth bearing in mind that research in theoretical linguistics has frequently been able to derive conclusions of general significance from the study of what appear at first glance to be quirks of the grammar. Following this tradition, the goal of this volume is to present recent research into parenthesis and ellipsis phenomena and heir interactions, in order to advance our understanding of grammar as a whole. We will now briefly highlight the main issues raised by each empirical domain, then show how investigating their intersection can help illuminate them.